Peran Celebrity Endorser, Online Customer Review, Dan Harga Terhadap Keputusan Pembelian Pada Marketplace Shopee - Harijono, Dyah Alifia Wulandhari; Indayani, Lilik; Kusuma, Kumara Adji (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
The purpose of the research is to ascertain how charges, peer feedback on the internet, and famous brand ambassadors all affect what customers decide to make purchases. applying the quantitative approach in this investigation the approaches to data analysis utilized in this research consisted validity test, reliability test, normality test, classic assumption test, linear regression test, T test, F test, and R² test, that had been run by way of the software known as SPSS. The additional information needed over this investigation came from previous investigations, while the main information came from the assignment of survey forms via Google Form.